Female Leadership and Gender Gap within Firms: Evidence from an Italian Board Reform - Agata Maida; Andrea Weber (Institute of Labor Economics (IZA), 2019)
Over the last decade, several countries have followed the Norwegian example and introduced laws mandating gender quota for corporate board membership. The main aim of these laws is breaking the "glass ceiling" which prevents women from advancing into top corporate positions. In this paper, we evaluate the Italian law of 2011, which installed a step-wise increase in gender quota that remain effective for three consecutive board renewals of listed limited liability firms. We link firm-level information on board membership and board election dates with detailed employment and earnings records from the Social Security registers. Exploiting the staggered introduction of the gender quota regulation and variation in board renewals across firms, we evaluate the effect of the board gender composition on measures of gender diversity in top positions over a period of 4 years. While the reform substantially raised the female membership on corporate boards, we find no evidence of spillover effects on the representation of women in top executive or top earnings positions. Our results confirm the findings by Bertrand et al. (2019) who study the introduction of a gender quota for board members in Norway. Given that Italy is a much less egalitarian society than Norway, with a larger scope of establishing gender equality, our results confirm that board quota policies alone are ineffective in raising female representation in top corporate positions, at least in the short run.
Keywords: J24; J7; J78; 330; gender quota; corporate board reform; glass ceiling; female employment